Longing for God's closeness rediscovering the beauty of daily prayers - Ayesha Syahira (Iman Publication Snd Bhd, 2021)
What does it take to feel closer to Him when our daily prayers seem to falter? Oftentimes, there is this distant feeling within us when we meet God in our prayers. And it breaks our heart because we try so hard to connect to Him, yet we are just distracted with the worries of this world. What then can we do, to reawaken this longing for closeness to Him, the longing to rely on His forgiveness and mercy? It is not easy to call upon the heart to be present in prayers. We try our best to connect to Him, but still we find our mind wandering someplace else. Thus, in this book, Ayesha Syahira shares with raw honesty about her reflections on discovering the beauty of prayers through patience, surrendering and hope.